Grupos principales del zooplancton durante El Niño 1992-93 en el Canal de San Lorenzo, Golfo de California - Lavaniegos E., Bertha E. (1999)
The structure by groups of zooplankton (generally Class or Order) from the San Lorenzo Channel, Gulf of California is described during 1990 and the ENSO 1992-93. The samples were collected with a bongo net of 300 and 500 μm of mesh width. Significant differences in abundances estimated with the two kinds of meshes were found in ten zooplankton groups. Per example, copepods. chaetognaths and siphonophores were underestimated betwecn 21 and 34% with the 500 μm net, compared to the 300 μm. Other groups of smaller size, as appendicularians, thecosomes, foraminiferans and radiolarians, were underestimated in more than 50%. For the meroplankton, bivalve larvae had a mean abundance 96% lower with the 500 μm net. The comparison between spring-summer samples (from the 300 μm net) of 1990 and 1992 indicated a lower incidence of appendicularians and thaliaceans in 1992, while the ostracods increased. These changes may be due to the warrrllng of water by the ENSO 1992-93, a surface temperature 2°C higher was observed in August 1992 compared to August 1990.